2022
DOI: 10.1002/alz.12867
|View full text |Cite
|
Sign up to set email alerts
|

Functional network segregation is associated with attenuated tau spreading in Alzheimer's disease

Abstract: Introduction Lower network segregation is associated with accelerated cognitive decline in Alzheimer's disease (AD), yet it is unclear whether less segregated brain networks facilitate connectivity‐mediated tau spreading. Methods We combined resting state functional magnetic resonance imaging (fMRI) with longitudinal tau positron emission tomography (PET) in 42 betamyloid‐negative controls and 81 amyloid beta positive individuals across the AD spectrum. Network segregation was determined using resting‐state fM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 58 publications
2
19
0
Order By: Relevance
“…Our second main finding revealed that ApoE4 was not only associated with accelerated tau accumulation through higher Aβ levels, but also had possible synergistic effects with Aβ on tau spreading, congruent with cross-sectional evidence of higher tau PET at given level of Aβ in ApoE4 carriers . Specifically, we demonstrated that the rate of Aβ-related tau accumulation was moderated by ApoE4 across regions vulnerable to early-stage tau aggregation and spread (ie, in regions strongly connected to tau epicenters Q1-Q2) . These results are congruent with a biphasic AD pathophysiological framework, which proposes an Aβ-dependent then a later Aβ-independent tau accumulation phase, supported by mouse model evidence demonstrating that Aβ-targeting antibodies reduced early but not later tau changes .…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Our second main finding revealed that ApoE4 was not only associated with accelerated tau accumulation through higher Aβ levels, but also had possible synergistic effects with Aβ on tau spreading, congruent with cross-sectional evidence of higher tau PET at given level of Aβ in ApoE4 carriers . Specifically, we demonstrated that the rate of Aβ-related tau accumulation was moderated by ApoE4 across regions vulnerable to early-stage tau aggregation and spread (ie, in regions strongly connected to tau epicenters Q1-Q2) . These results are congruent with a biphasic AD pathophysiological framework, which proposes an Aβ-dependent then a later Aβ-independent tau accumulation phase, supported by mouse model evidence demonstrating that Aβ-targeting antibodies reduced early but not later tau changes .…”
Section: Discussionsupporting
confidence: 85%
“…Group demographic characteristics were compared using analyses of variance for continuous and χ 2 tests for categorical variables. ROI-specific annual tau PET change rates were estimated using linear mixed models with longitudinal tau PET SUVR values as the dependent variable and time from baseline as the independent variable, including random slope and intercept …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…PCA and LPA differ in their most prominent sites of initial tau deposition on tau‐PET. Assuming that tau spreads trans‐synaptically, the accumulation of tau pathology over time might be facilitated when the regions with high tau burden are functionally connected to the rest of the brain, with a slower spreading if such regions are instead part of segregated networks 12 . This would lead to differences in rates of tau accumulation between PCA and LPA.…”
Section: Introductionmentioning
confidence: 99%